Teaching family medicine residents about care of adults with intellectual and developmental disabilities - Casson, Ian (Can Fam Physician, 2019)
PROBLEM ADDRESSED: Adults with intellectual and developmental disabilities (IDD), a group with complex health problems and inequities in access to health care, look to family physicians for primary care. OBJECTIVE OF PROGRAM: To enable residents to learn and demonstrate competencies that are unique to the care of adults with IDD with minimal extra time and resources required of the residency program. PROGRAM DESCRIPTION: In their regular family medicine teaching practices, residents undertake planned encounters with adults with IDD involving comprehensive health assessments with physical examinations. Tools to implement the Canadian guidelines for primary care of adults with IDD are available to support the residents in their encounters. Background information in the form of self-learning and small group learning resources, field notes with rubrics to assess residents’ development of competencies, and faculty development resources are also available. CONCLUSION: It is important to include such planned clinical experiences in family medicine residency curricula because people with IDD have special needs that are difficult to learn about in other settings. It is a benefit to residents to have patients and families actively contributing to teaching.